KINERJA ORGANISASI DALAM PEMBUATAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DI KANTOR KECAMATAN DOLO KABUPATEN SIGI - Nurtin, Nurtin (Katalogis, 2014)
The purpose of this study is to describe and analyze the organization performance in theproduction of Electronic Identity Card (e-ID) at the Subdistrict Office of Dolo, Sigi Regency. The technic to selecting informants is purposive, which has selected six people and data collection is by observation, interviews, and documentation. Technic analyze of data is with data reduction, data display and get conclusion. The results of this study showed that organization performance in the production of Electronic Identity Card (e-ID) at the Subdistrict Office of Dolo, Sigi Regency were based on five indicators that is productivity, quality of service, responsiveness, responsibility and accountability in the whole is already be good classified but can’nt called maximized. This because the result of recorder is still remote from target performance which certain before. In the addiction, to  much  case  be  necessary  to  notice  and  to  enhance  by  subdistrict  head  and  employees  in particulary within to determined the wisdom that not just appropriate with situation and condition of  local  society but should be more efficient and effective so what that be the purpose before can be reach better at the properly time.